Squamoid Cyst of Pancreatic Ducts: A Challenging Differential Diagnosis among Benign Pancreatic Cysts - Milanetto, Anna Caterina; Iaria, Loredana; Alaggio, Rita; Pedrazzoli, Sergio; Pasquali, Claudio (JOP. Journal of the Pancreas, 2013)
Context In the last years, cystic pancreatic lesions are often detected when clinically silent, because of the wider use of diagnostic imaging techniques. First described by Othman in 2007, “squamoid cyst of pancreatic ducts” represents a cystic dilation of ducts, lined by non-keratinized squamous epithelium. We report the first case of squamoid cyst of pancreatic ducts in Italy. Case report A 68-year-old woman presented a cystic lesion (4 cm) of the pancreatic tail as incidental finding at MRI. It had a thickened wall, no internal septa and no communication with the Wirsung duct were detected. A CT scan showed a lamellar calcification on its posterior wall. A 18F-FDG-PET was negative. Blood tests were normal, including CEA and CA 19-9. We performed a spleen-preserving distal pancreatectomy. Histology showed a unilocular cyst, with serous fluid and a fibrous wall, with multilayered epithelium without cytological atypias. Immunohistochemistry showed CK 7 positive and CK 5 negative. The patient is still alive and without disease after 42 months of follow-up. Conclusions In the English literature only seven cases resected for this cyst type have been reported. No preoperative test can achieve a definitive diagnosis, so surgical resection remains the treatment of choice in order to exclude malignancy. However, after intraoperative frozen section, a limited pancreatic resection can be performed. Image: CT scan showing a 4 cm cystic fluid mass arising from the tail of the pancreas.